Epilithic diatom of the güvercinlik pond (Arguvan/ malatya, turkey) - Caglar, M.; Selamoglu, Z. (Green Wave Publishing of Canada, 2021)
In this study, the epilithic diatoms of the Güvercinlik Pond, which is located in Arguvan, Malatya, were investigated between March and November of 2016. During the study, a total of 39 taxa, 3 belonging to centric diatoms and 36 belonging to pennate diatoms, were recorded. The diatom types represented by the highest number of species were Cymbella (5 taxa), Nitzschia (4 taxa) and Navicula (7 taxa). Diatoms showed their best growth in late spring and summer, when water temperature and light began to increase. Sorensen similarity index between the diatoms at both stations was found as 58.18%. © 2021, Green Wave Publishing of Canada. All rights reserved.
Keywords: Diatom; Epilithic; Güvercinlik; Malatya-Turkey; Pond